Education for rural people : the role of education, training and capacity development in poverty reduction and food security - Acker, David (Food and Agriculture Organization of the United Nations, 2009)
Nearly one out of six people in the world is suffering from hunger and illiteracy. This book was developed to assist policy makers dealing with rural poverty, food insecurity and education challenges confronting rural people. It seeks to address the correlation between education, training, empowerment and food security, mainly through a number of examples from all over the world. It is about strengthening the capacity of rural people to achieve food security. It identifies different dimensions of education and training that have proven useful, and covers formal education as well as non-formal education, literacy as well as skills training.--Publisher's description.